Tyrosine hydroxylase variants influence protein expression, cellular localization, stability, enzymatic activity and the physical interaction between tyrosine hydroxylase and GTP cyclohydrolase 1 - Jung-Klawitter, Sabine; Richter, Petra; Yuan, Yuheng; Welzel, Karin; Kube, Marie; Bähr, Stella; Leibner, Alexander; Flory, Egbert; Opladen, Thomas (Journal of inherited metabolic disease, 2024)
Tyrosine hydroxylase (TH) is the rate-limiting enzyme in dopamine biosynthesis catalyzing the tetrahydrobiopterin (BH4)—dependent hydroxylation of tyrosine to L-DOPA. Here, we analyzed 25 TH variants associated with various degrees of dopa-responsive dystonia and evaluate the effect of each variant on protein stability, activity and cellular localization. Furthermore, we investigated the physical interaction between TH and human wildtype (wt) GTP cyclohydrolase 1 (GTPCH) and the effect of variants on this interaction. Our in vitro results classify variants according to their resistance to proteinase K digestion into three groups (stable, intermediate, unstable). Based on their cellular localization, two groups of variants can be identified, variant group one with cytoplasmic distribution and variant group two forming aggregates. These aggregates do not correlate with loss of enzymatic activity but nevertheless might be a good target for molecular chaperones. Unfortunately, no obvious correlation between the half-life of a variant and its enzymatic activity or between solubility, stability and enzymatic activity of a given variant could be found. Excitingly, some variants disrupt the physical interaction between TH and human wildtype GTPCH, thereby interfering with enzymatic activity and offering new druggable targets for therapy. Taken together, our results highlight the importance of an in-depth molecular analysis of each variant in order to be able to classify groups of disease variants and to find specific therapies for each subgroup. Stand-alone in silico analyses predict less precise the effect of specific variants and should be combined with other in vitro analyses in cellular model systems.